BRANDING BERAS DI DESA BURUAN SEBAGAI SOLUSI UNTUK MENINGKATKAN HARGA JUAL BERAS - Astari, Ni Komang Puspita; Apriantara, I Gede Agus; Tampubolon, Anggada Hardoyogi (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The length of the rice distribution chain causes the selling price in farmers to be low while the selling price in the market is much higher, the difference in the selling price thus needs not to benefit farmers as small producers. Buruan Village, one of the villages in Penebal District, Tabanan Regency, Bali Province, still uses a third-party service, namely, middlemen, in the rice distribution channel. Farmers in Buruan Village increase the value of selling rice by changing these distribution channels and improving farmer ties to manage and distribute rice produced by independent local farmers. To realize the things that need to be supported by the preparation and maturity of management, there is no exception in terms of branding that will characterize Buruan's local identity. Branding itself can increase public awareness of products that are widely known by potential buyers and consumers. In this case, there are three uns branding stored, namely, packaging, logo, and tagline. In this modern era, these three things are essential to boost a finished product, and the selling value can be higher than the market.